2009
DOI: 10.1186/1471-2148-9-55
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of divergently-paired genes (DPGs) among Drosophila and vertebrate genomes

Abstract: Background: Divergently-paired genes (DPGs) are defined as two adjacent genes that are transcribed toward the opposite direction (or from different DNA strands) and shared their transcription start sites (TSSs) less than 1,000 base pairs apart. DPGs are products of a common organizational feature among eukaryotic genes yet to be surveyed across divergent genomes over well-defined evolutionary distances since mutations in the sequence between a pair of DPGs may result in alternations in shared promoters and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 65 publications
3
32
1
Order By: Relevance
“…Tip60/NuA4 binds to the cycB promoter and 59 intron, suggesting that cycB could be directly regulated by NuA4 (Filion et al 2010). Interestingly, cycB is located in the genome as a divergently paired gene (DPG) (Yang and Yu 2009) with stall, which is upregulated 6.5-fold upon Tip60 inhibition. Tip60/NuA4 may therefore act to direct the proper transcription of certain DPGs with differential expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Tip60/NuA4 binds to the cycB promoter and 59 intron, suggesting that cycB could be directly regulated by NuA4 (Filion et al 2010). Interestingly, cycB is located in the genome as a divergently paired gene (DPG) (Yang and Yu 2009) with stall, which is upregulated 6.5-fold upon Tip60 inhibition. Tip60/NuA4 may therefore act to direct the proper transcription of certain DPGs with differential expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…If coexpression of close head-to-head gene pairs provides lower fitness, selection should favor rearrangements that result in physical or functional separation of the two genes. A comparative analysis of head-to-head gene pairs in different species revealed that these pairs are more conserved in vertebrate lineage than in Drosophila species (Yang and Yu 2009;Weber and Hurst 2011). Drosophila has more close head-to-head gene pairs than mammals, but the conservation of these pairs is threefold lower (Yang and Yu 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis of head-to-head gene pairs in different species revealed that these pairs are more conserved in vertebrate lineage than in Drosophila species (Yang and Yu 2009;Weber and Hurst 2011). Drosophila has more close head-to-head gene pairs than mammals, but the conservation of these pairs is threefold lower (Yang and Yu 2009). This suggests that some of the head-to-head gene pairs in Drosophila arise from genome compaction rather than selection for this specific organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations